Regional Power Role and Intervention: The Turkish Case Over Syria in the 2000s - SEVER, AYŞEGÜL (SAGE PUBLICATIONS INC, 2020)
The article elaborates how Turkey's relations with Syria, which have been pursued by varying foreign policy instruments and conduct, have greatly affected Turkey's standing on the Middle East during the 2000s. By employing the relevant concepts, regional power and third party intervention in the literature, the article aims to explain the changes caused by the Syrian conflict in the AKP's (Adalet ve Kalkinma Partisi-the Justice and Development Party) foreign policy in a better frame. After the Syrian conflict, Turkey's increasing intervention in Syria including use of force resulted in a new power projection other than soft power in its regional relations. Neighboring a civil war state caused Ankara to organize its relations with Syria and the Middle East in a new context which requires new mechanisms, new partnerships, and new interpretations in the face of rising nongovernmental armed groups, refugee flows, changing regional alignments, and diverging interests with its major Western allies.
Keywords: Turkey; Syria; foreign policy; Syrian crisis; mediation; FOREIGN-POLICY; FAILED STATES; SOFT POWER; TURKEY; IDENTITY; POLITICS; BORDER